Versatile carboxylate-directed structures of ten 1D → 3D Ni(ii) coordination polymers: fluorescence behaviors and electrochemical activities. Issue 35 (14th August 2019) - Liu, Guocheng; Li, Yan; Lu, Zhenjie; Li, Xiaowu; Wang, Xiuli; Wang, Xiang; Chen, Xingxing
Abstract : Ten 1D → 3D Ni(ii ) coordination polymers based on a phenyl/methylene-mixed-bridged ligand have been obtained and structurally directed by carboxylates; they show different fluorescence behaviors and electrochemical activities. Abstract : To study the effects of carboxylates on the assembly and structures of Ni(ii ) coordination polymers (CPs) based on a phenyl/methylene-mixed-bridged bis-pyridyl-bis-amide [ N, N ′-bis(4-methylenepyridin-4-yl)-1, 4-benzenedicarboxamide] (L) ligand, ten 1D → 3D Ni(ii ) CPs, namely [Ni(L)(2-NB)2 (H2 O)2 ] (1 ), [Ni(L)(4-NB)2 (H2 O)2 ] (2 ), [Ni(L)2 (2-MOB)2 ] (3 ), [Ni(L)2 (3-CB)2 ] (4 ), [Ni(L)(2-CP)(H2 O)] (5 ), [Ni(L)(5-NIP)(H2 O)2 ]·2H2 O (6 ), [Ni(L)(3-NP)(H2 O)2 ] (7 ), [Ni(L)(4, 4′-OBA)]·H2 O (8 ), [Ni(L)(1, 4-BDC)(H2 O)2 ]·2H2 O (9 ) and [Ni(L)(1, 4-CHDA)(H2 O)2 ]·4H2 O (10 ) [2-nitrobenzoic acid (2-HNB), 4-nitrobenzoic acid (4-HNB), 2-methoxybenzoic acid (2-HMOB), 3-chlorobenzoic acid (3-HCB), 2-carboxyphenylacetic acid (2-H2 CP), 5-nitroisophthalic acid (5-H2 NIP), 3-nitrophthalic acid (3-H2 NP), 4, 4′-oxybis(benzoic acid) (4, 4′-H2 OBA), 1, 4-benzenedicarboxylic acid (1, 4-H2 BDC) and trans -1, 4-cyclohexanedicarboxylic acid (1, 4-H2 CHDA)], have been hydrothermally synthesized with various carboxylates and structurally characterized by IR, PXRD and X-ray single-crystal diffraction.1 and2 are similar 1D coordination polymers.3 and4 feature similar 2D coplanar 4, 4-connected networks extended by single L linkers.5 displays a 2D wave-like 4, 4-connected network based on L and 2-CP mixed linkers.6 shows a 2D 4, 4-connected structure derived from L and 5-NIP mixed spacers.7 is a CdSO4 type 4-connected 3D framework.8 displays a 2D → 3D parallel polycatenation array based on 2D (4, 4)-connected wave-like coordinated layers.9 and10 feature similar 2D → 3D inclined polycatenation arrays based on 2D (4, 4)-connected coplanar networks. The effects of the carboxylates on the structures of the title complexes are discussed in detail. The solid-state luminescent and fluorescent sensing properties of1–10 for Fe 3+ ions were investigated. Moreover, the effects of1, 5 and7 on the fluorescence properties of bovine serum albumin (BSA) and the electrocatalytic activities of carbon paste electrodes (CPEs) bulk-modified with1, 3, 5, 7 and9 for the reduction of hydrogen peroxide, bromate and nitrite were studied.